Strategy in Developing Teacher Professionalism Competency to Improve Education Tadika Malay School in South Patani Thailand - Taye, Ainham; Kasdi, Abdurrahman (QUALITY, 2022)
This study aims to find out in depth about how the Perkasa Institute leadership strategy steps in developing teacher professional competence to improve the quality of education in schools Malay TADIKA. The type of research conducted by the author is field research, the approach used is a qualitative approach. The sources in this research data are primary data sources and secondary data sources. The data collection technique of this research is interviews, observation, documentation, using inductive qualitative data analysis techniques. While the data validity test uses triangulation, namely re-examination of data that has been obtained previously with different techniques or sources than before. The results of this study indicate that: The leadership steps of the Perkasa Institute in relation to developing the competence of a teacher with good goals for them are as follows; a. Discipline at work, b. Generating work motivation, c. Awards in improving work, d. Holding Teacher Training Seminars, e. Hold a Curriculum Development Seminar. Strategi Pengembangan Kompetensi Profesionalisme Guru untuk Meningkatkan Pendidikan Sekolah Tadika Melayu di Patani Selatan Thailand. Penelitian ini bertujuan untuk mengetahui secara mendalam tentang  bagaimana Konsep, langkah-langkah strategi kepemimpinan Lembaga Perkasa dalam Peningkatan profesionalisme guru agama Berbasis Nilai Islam Melayu Patani di Sekolah Melayu TADIKA. Adapun jenis penelitian yang dilakukan oleh penulis adalah penelitian lapangan, pendekatan yang digunakan adalah pendekatan yang bersifat kualitatif. Sumber dalam data penelitian ini adalah sumber data primer dan sumber data sekunder. Teknik pengumpulan data penelitian ini dengan wawancara, observasi, dokumentasi, dengan mengunakan teknik analisis data kualitatif yang bersifat induktif. Sedangkan uji keabsahan data menggunakan triangulasi Yaitu pemeriksaan kembali terhadap data yang sudah didapatkan sebelumnya dengan teknik atau sumber yang berbeda dari sebelumnya. Hasil penelitian ini menunjukkan bahwa: a. Pembinaan disiplin dalam kerja, b. Membangkitkan motivasi kerja, c. Penghargaan dan peningkatan kerja, d. Mengadakan seminar Pelatihan guru, e. Mengadakan seminar pengembangan kurikulum.